The Effect of Promotion Through the Shopee Marketplace on Purchasing Decisions of Scarlett Body Lotion among Students (Productivity, 2024)
The purpose of this study was to determine the effect of promotion on purchasing decisions. This type of research is descriptive quantitative, using a correlation approach and simple linear regression. The population in this study were students from the Faculty of Social and Political Sciences, Sam Ratulangi University Manado with sample criteria, namely students who have used or bought Scarlett Body Lotion products at Shopee, have bought similar products from the Scarlett Whitening brand, and have seen or visited advertisements about these products at Shopee. The research sample consisted of 97 respondents using a Likert scale questionnaire instrument. The results of the research in the t test show that there is a significant and positive effect of Promotion on Purchasing Decisions.